Documentation of acute change in mental status in nursing homes highlights opportunity to augment infection surveillance criteria. (28th July 2020) - Penna, Austin R.; Sancken, Christina L.; Stone, Nimalie D.; Eure, Taniece R.; Bamberg, Wendy; Barney, Grant; Barter, Devra; Carswell, Stacy; Clogher, Paula; Dumyati, Ghinwa; Felsen, Christina B.; Frank, Linda; et al.
Abstract: Acute change in mental status (ACMS), defined by the Confusion Assessment Method, is used to identify infections in nursing home residents. A medical record review revealed that none of 15, 276 residents had an ACMS documented. Using the revised McGeer criteria with a possible ACMS definition, we identified 296 residents and 21 additional infections. The use of a possible ACMS definition should be considered for retrospective nursing home infection surveillance.